Concurrent Occurrence of Developmental Anomalies— Dens Evaginatus and Dens Invaginatus in Maxillary Lateral Incisor: Report of Two Cases - Gehlot, Paras Mull; Manjunath, Vinutha; Manjunath, MK (Journal of Orofacial Research, 2012)
Developmental anomalies affecting tooth morphology are common in the literature. Dens evaginatus (DE) occurring in anterior tooth, termed ‘talon cusp’ is a relatively rare developmental anomaly. It presents as an additional cusp that project predominantly from the lingual surface of primary or permanent anterior teeth. Dens invaginatus (DI) is a developmental anomaly resulting from infolding of the tooth crown or root before calcification has occurred. Concurrent occurrence of DE and DI within the same tooth is rare. The present article reports two cases with concurrent occurrence of DE and DI in permanent maxillary lateral incisor. In case 1 the DE and DI are associated with nonvital tooth and in case 2 the DE and DI are associated with a vital tooth. The management aspects are discussed.